2006
DOI: 10.1163/156856806776923416
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of color and figure–ground effects in the watercolor illusion

Abstract: Two phenomena can be observed in the watercolor illusion: illusory color spreading and figureground organization. We performed experiments to determine whether the figure-ground effect is a consequence of the color illusion or due to an independent mechanism. Subjects were tested with displays consisting of six adjacent compartments, three that generated the illusion alternating with three that served for comparison. In a first set of experiments, the illusory color was measured by finding the matching physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Under these conditions, the border ownership is weakened and the figure–ground segregation appears reversible. This result suggest that figure–ground and depth segregation are independent from the coloration effect (Pinna, 2005; Pinna and Reeves, 2006; von der Heydt and Pierson, 2006). Pinna (2005) and Pinna and Reeves (2006) introduced the “asymmetric luminance contrast principle” (Pinna, 2005) stating that, all else being equal, given an asymmetric luminance contrast on both sides of a contour, the region, whose luminance gradient is less abrupt, is perceived as a figure if compared to the complementary more abrupt region perceived as a background.…”
Section: Results: Shape and Color Organizationmentioning
confidence: 90%
See 2 more Smart Citations
“…Under these conditions, the border ownership is weakened and the figure–ground segregation appears reversible. This result suggest that figure–ground and depth segregation are independent from the coloration effect (Pinna, 2005; Pinna and Reeves, 2006; von der Heydt and Pierson, 2006). Pinna (2005) and Pinna and Reeves (2006) introduced the “asymmetric luminance contrast principle” (Pinna, 2005) stating that, all else being equal, given an asymmetric luminance contrast on both sides of a contour, the region, whose luminance gradient is less abrupt, is perceived as a figure if compared to the complementary more abrupt region perceived as a background.…”
Section: Results: Shape and Color Organizationmentioning
confidence: 90%
“…Furthermore, Zhou et al (2000) reported that approximately half of the neurons in the early cortical areas are selective in coding the polarity of color contrast. The same correlate can be assumed to explain the figure–ground effect of the watercolor illusion (von der Heydt and Pierson, 2006). The specialized phenomenal roles of the juxtaposed and displaced contours in boundary and color and the phenomenal logic of their organization can shed light to understand how neurons become more and more specialized by firing to only one attribute and how they are then integrated, after a level of juxtaposition of attributes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Given that such induction effects often occur together with changes in the perceived depth of either the inducing field or the test field, as in the watercolor illusion (e.g. Pinna and Reeves, 2006;von der Heydt and Pierson, 2006), we compared probabilities of simultaneous induction with the probabilities that the patterns which generate them are seen as nearer to the observer. In fact, inducers with a stronger tendency to be perceived as separated in depth from their immediate backgrounds may also have a stronger tendency to produce induction effects in terms of apparent contrast.…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions, we suggest introducing along the contours some variations as demonstrated by the watercolor illusion (Devinck et al 2005; Pinna 1987, 2005, 2008b; Pinna and Grossberg 2005; Pinna et al 2001; Pinna et al 2003; Spillmann et al 2004; von der Heydt and Pierson 2006; Werner et al 2007; Wollschläger et al 2002). The set of figural properties emerging from this illusion depends on two factors: the juxtaposition of contours and the formation of asymmetrical luminance and chromatic conditions along the contours.…”
Section: Boundary Color Shading and Lighting Contoursmentioning
confidence: 99%